Flexible Microwave Tag System Based on DGS Multiple Resonators - Seok-Jae Lee; Jongsik Lim; Dal Ahn; Sang-Min Han (International Journal of Antennas and Propagation)
A new flexible microwave tag system using a frequency-scanning type RFID is proposed with multiple resonators based on defected ground structures (DGSs). The proposed system achieves fully passive tag systems using multiple resonators with a spiral-shaped DGS over a wide frequency range. The resonator implemented on the rear side of a transmission line has the advantages of excellent band notch characteristics as well as bit-error avoidance from the frequency selective reflection. In addition, the tag system is designed on a thin flexible substrate in order to be applicable for amorphous surfaces. The proposed microwave tags have been implemented with wideband antennas at 3–7 GHz on thick and thin flexible substrates. The flexibility of the thin substrate has been evaluated in terms of cognitive capability for various radiuses of curvatures. From the experimental results in an anechoic chamber, the excellent recognition of various multibits identification codes in a wireless transmission environment has been verified.